Impact mitigating capabilities of a spray-on elastomer coating applied to concrete. (June 2019) - Fallon, C.; McShane, G.J.
Highlights: Dynamic impact experiments are performed on elastomer-coated concrete. An elastomer coating significantly reduces impact damage in the concrete substrate. Numerical modelling suggests the elastomer alters damage initiation in the concrete. Abstract: Structural protection against the effects of a nearby explosive detonation is an area of growing importance. Spray-on elastomer coatings are of interest as a practical and low cost protective solution. Recent research has demonstrated the effectiveness of such coatings for blast mitigation. However, there are two loading scenarios of concern for these applications: blast pressures and fragment impacts. To date, there remains a need to understand the merits of this protective solution for impact indentation of concrete structural elements. In this work, we examine whether, and by what mechanism, an elastomer coating can offer protection in this case. A series of quasi-static indentation and dynamic impact experiments are performed using a 0.1 kg circular cylindrical ( i.e. blunt) projectile. It is demonstrated that the coating displays a significant protective capability over the full range of impact velocities considered, c. 45–150 m s − 1 . The coating remains intact until impacted at a velocity of c.120 m s − 1 when it fails by a ductile, tearing mechanism, forming a plug which undergoes large elastic contraction after projectile penetration. A finite element model of the impact indentation of uncoated and coated concrete cubes is developed and validated against the experiments. Focusing on the early time steps and damage initiation in the concrete, the numerical model is used to interrogate the mechanism by which the elastomer achieves its mitigating effect. It is found that the way in which the elastomer alters the stress distribution in the concrete, and its time evolution, is key to its performance. These findings provide a basis for optimising protective coatings for concrete structural elements.